PENGARUH KUALITAS LAYANAN, FASILITAS DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL “ANEKA MOTOR SERVICE” WARU - SIDOARJO - Shindu Hargo Dedali (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
ABSTRACT In an era of very difficult progress, more and more companies are competing to get a good market segment to increase input in their business. In this case the company must be able to understand the needs and desires of customers. One business that also feels the tight competition is the workshop "Aneka Motor Service Waru - Sidoarjo" In this case the company must be able to understand the needs and desires of customers. The technique used in this study is the accidental sampling method by distributing questionnaires as many as 80 respondents. Distribution of questionnaires is done in stages for 2 weeks until the data collection process is fulfilled. Keywords: Service Quality, Facilities, Company Image, Customer Satisfaction